HUBUNGAN KARAKTERISTIK, PENGETAHUAN DAN SIKAP IBU DENGAN PEMBERIAN MP-ASI PADA BAYI DI WILAYAH KERJA PUSKESMAS SIANTAN TENGAH - ., Winda Septia Khairunnisa (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2013)
Background. Child undernutrition in Pontianak has increased in 2010 andmost cases were found in Puskesmas Siantan Tengah. It is reflection ofmothers suboptimal care and feeding practices. Mothers behaviour whichis affected by her characteristics is formed by knowledge and attitude.Objective. To analye about the relationship between motherscharacteristics, knowledge and attitude with infant complementary feedingpractices in Puskesmas Siantan Tengah Working Area.Methodology. This study was analytic study with cross sectional approach.Population was all mothers of 6-11 month old babies who lived inPuskesmas Siantan Tengah working area in 2013. Samples were 81mothers who were selected by probability. The data was result ofinterviews based on questionnaire and were analyed by Chi-Square test.Result. This study shows that age (p= 0,045), familys income (p= 0,007),and knowledge (p= 0,008) can influence infant feeding practices, whereasvariables which can not influence the behaviours were ethnic, religion,education level, working history, working duration, number of children andmothers attitude.Conclusion. It is suggested that age, familys income, and knowledgeinfluence the complementary feeding practices in Puskesmas SiantanTengah working area in 2013.Keywords : mothers behaviour, nutrition, feeding practice